CONCRETE COMPOSITES USING GRAND-SANDY MIXTURES OF DEPOSITS OF THE CHECHEN REPUBLIC - A. Kh. Alaskhanov; S.-A. Yu. Murtazaev; M. S. Saidumov; M. S.-M. Khubaev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Development of optimal recipes of concrete mixtures using local natural raw materials in the form of gravel-sand mixtures from deposits of the Chechen Republic.Method The research methods adopted in the work are based on the theoretical principles and laws of designing and optimizing polydisperse multicomponent systems, the phase and structure formation of clinker minerals, the logic of mathematical calculations, the technological features of the structure formation of composite masses, the theoretical principles of controlling the rheological processes of mixes. All experimental data presented in the work were obtained according to the methods of current regulatory documents (GOST, recommendations, etc.).Result The paper presents the results of a study of the composition and properties of sand and gravel mixtures of deposits of the Chechen Republic and concretes based on them. In particular, the granulometric and chemical compositions and the physicomechanical properties of sand and gravel mixtures have been studied. An analysis of the scientific literature and experience in the use of sand and gravel in construction. The leading scientific schools of the country and abroad in the field of concrete science are presented. The rheological indices of concrete mixes were studied and the dynamics of the curing of concrete of different classes were obtained on the basis of unfortified sand and gravel mixtures in the presence of a chemical additive, the superplasticizer Polyplast SP-1.Conclusion It is proposed to use sand-gravel in its natural form in concrete for non-critical structures in its natural form without additional costs for enriching its composition. The feasibility of obtaining low-grade concrete with the use of sand and gravel mixtures without its enrichment and fractionation is established.